Inovasi Pelayanan E-Ktp Berbasis Aplikasi Identitas Kependudukan Digital (IKD) Di Dinas Kependudukan Dan Pencatatan Sipil Kota Tangerang - Fikri Pramudya Putra; Agus Suherman; Fitri Firdayani (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
This study aims to find out the innovation of E-KTP services through digital population identity applications. And to find out what factors are driving and inhibiting the application of a digital identity. In this study, the authors used a qualitative descriptive approach. This study uses qualitative data types, which consist of primary and secondary data. The data collection used is observation/observation, interviews and documentation. The validity of the data according to qualitative research methods is as follows, Credibility Test, Transferability Test, Dependability Test and Confirmability Test. Data collection techniques include data collection, data reduction, data display and conclusion drawing. The results of the research show that the innovation of E-KTP services through the IKD application, of the five variables, shows that the Relative Advantage indicator can be said to be good because the community can feel the benefits. Meanwhile, the indicators of Compatibility (appropriateness), Complexity (complexity), Triability (possibility of trying), and Observability (ease of observation) need to be improved again. The driving and inhibiting factors of IKD applications. The driving factor is being able to provide services via mobile phones so as to provide convenience for the community. And the data is integrated with population data and data security is protected. While the inhibiting factors are, the IKD application has not been integrated by other agencies such as Banks and Immigration, Not all people have cellphones that are compatible with the IKD application and the lack of outreach from the Department of Population and Civil Registration regarding the procedures and benefits of the IKD application.